Factors that Influence People to Take Loans from Mobile Banks - Arrizky, Bintang Juannita; Adinugraha, Hendri Hermawan (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2024)
Economics is one of the problems experienced by humans in their daily lives, especially in terms of meeting needs. Humans must fulfill all their complex needs to survive. Human needs are very diverse and tend to always change from time to time. This situation is influenced by the nature of humans themselves who tend to never feel satisfied with what they have obtained. This article aims to analyze the behavior of people who borrow from roving banks and the problems that occur due to the existence of these banks for the public. Among the middle and lower economic classes, roving banks are quite popular because they provide easy loan services and fast processing. This convenience makes people idolize mobile banks because they provide emergency money and are welcomed by the public. For this reason, this article contains a discussion of how the behavior of the public, especially for those who borrow money from roving banks, and what factors are behind mothers borrowing from roving banks. This research uses a descriptive qualitative method. This method was chosen because the author intends to describe and explain the factors that influence people to make loans to roving banks. Based on the results of the discussion, many people are ensnared by this roving bank. Many problems arise, ranging from the family economy getting strangled, the destruction of family relationships, to social relationships with neighbors becoming less good. This happens because many people borrow from more than one bank and use the names of other people who have never borrowed from the bank. So that many people are ultimately ensnared by the practice of digging holes to pay these debts